Pan-genome and reverse vaccinology for a multi-epitope vaccine against circulating post-2022 Monkeypox virus strains - Md Al Saber; Md. Hasan Jafre Shovon; Md. Imtiaz; Sadia Jannat Tauhida; Sowmitro Das; Md Mohaimenul Islam Tareq; Miss Ismoth Ara Tripty; Md Ridoy Hossain; Labib Shahriar Siam; Md Nazmul Hasan Zilani; Saifullah; S.M. Khaledur Rahman; et al. (PLoS ONE, 2026)
Background Since the 2022 outbreak, the number of Monkeypox cases worldwide has been increasing at an alarming rate. As of August 2024, approximately 99,000 people have been infected with the virus. The severity of this situation is further highlighted by the World Health Organization's (WHO) classification of the Mpox virus as a Public Health Emergency of International Concern (PHEIC) due to the increased fatality rate of approximately 3.6% in clade I. Objectives Targeting the virus's membrane-bound, enveloped, and extracellular proteins, our goal was to computationally develop and assess a broad-spectrum multi-epitope vaccine that elicits humoral and adaptive immune responses against Monkeypox virus (MPXV) infection. Methods During an outbreak, a pan-genome-based reverse vaccinology approach can offer rapid, practical solutions to enduring problems in experimental vaccine design. The method involved screening 16 monkeypox genomes to identify viral targets, from which viral proteins were selected based on their antigenicity, location, and solubility. Immunoinformatics methods and algorithms were used to extract the proteins’ putative T-cell and B-cell epitopes, which were combined to form several vaccine constructions. The tertiary structure of the chimeric vaccine construct's interaction with Toll-like receptor 4 (TLR4) was thoroughly assessed using the advanced techniques of molecular docking and molecular dynamics simulation. Results A pan-genomic analysis identified 80 core genes, which were then screened for proteins suitable for epitope-based vaccine design. From four of these selected proteins, T-cell and B-cell epitopes were extracted to create four distinct vaccine constructs. Appropriate adjuvants and linkers were incorporated into each construct to enhance its potential efficacy. Stability and immunogenicity analyses of each vaccine design yielded promising results. These findings suggest that the vaccine constructs could be effective in preventing monkeypox, warranting further experimental validation and supporting the application of similar strategies to combat other viral illnesses.